2019
DOI: 10.7249/rr2844
|View full text |Cite
|
Sign up to set email alerts
|

Co-Design of Services for Health and Reentry (CO-SHARE): An Experience-Based Co-Design (EBCD) Pilot Study with Individuals Returning to Community from Jail and Service Providers in Los Angeles County

Abstract: Limited Print and Electronic Distribution RightsThis document and trademark(s) contained herein are protected by law. This representation of RAND intellectual property is provided for noncommercial use only. Unauthorized posting of this publication online is prohibited. Permission is given to duplicate this document for personal use only, as long as it is unaltered and complete. Permission is required from RAND to reproduce, or reuse in another form, any of its research documents for commercial use. For inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
0
8
0
1
Order By: Relevance
“…As depicted in Figure 1 , few published sources (N=11) [ 16 26 27 89 90 91 92 93 94 95 96 ] report actual implementation of global ideas into local US communities to promote health equity or a related outcome. Most sources in this category are brief overviews of projects, and very few describe the full implementation and associated health equity outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As depicted in Figure 1 , few published sources (N=11) [ 16 26 27 89 90 91 92 93 94 95 96 ] report actual implementation of global ideas into local US communities to promote health equity or a related outcome. Most sources in this category are brief overviews of projects, and very few describe the full implementation and associated health equity outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Outcomes included increased social participation in health [92]; HIV access and treatment outcomes [95]; health care disparities, and social participation for underrepresented groups [89,96]; community engagement outcomes [27]; community resilience and, wellbeing [90]; mental health [89]; and social isolation [26]. First, all agreed that the field of global learning is nascent and evolving and requires a unifying name.…”
Section: Global Learning Initiatives Implemented In the Usmentioning
confidence: 99%
“…66 More recently, projects were undertaken with mothers or caregivers of malnourished or HIV-positive children and healthcare workers in a South African township, 70 and with formerly incarcerated prisoners in Los Angeles focusing on better integrating local health and social care services to support re-entry into the community. 71 Green et al's systematic review of EBCD found increasing reports in the peer-reviewed literature from 2014 onwards. 72 The majority of the 20 studies in the review were conducted in hospital settings in the UK, mostly in mental health, cancer, and paediatrics.…”
Section: Dissemination Of Ebcdmentioning
confidence: 99%
“…A variety of models are emerging, including those that seek to engage service user experiences in the program design process (Greenhalgh et al 2016;West 2019). While not yet widely applied in the criminal justice system, examples do exist. A recent pilot project in Los Angeles engaged people returning to the community from prison together with providers of health, social and justice services to identify priority areas for improvement, test promising ideas in service delivery and assess the feasibility of using the co-design process in other jurisdictions (Mendel et al 2019). The results of this project are not yet available.…”
Section: The Importance Of Lived Experience In the Policy Processmentioning
confidence: 99%